First record of Ciocalypta Bowerbank, 1862 (Demospongiae, Suberitida, Halichondriidae) in the Eastern Pacific, with description of a new species from Peru - Arroyo, Yessenia; Hajdu, Eduardo; Willenz, Philippe; Cóndor-Luján, Báslavi (Zootaxa, 2020)
Ciocalypta includes species with finger-shaped fistules emerging from a basal mass and skeleton composed by a central axis and secondary tracts supporting the ectosome. Although worldwide distributed, no species of this genus has been reported from the Eastern Pacific. In this study, a new Ciocalypta is described from shallow waters of the southern coast of Peru. Ciocalypta magnastyla sp. nov. is greenish white, possesses the typical fistules with oscula located at their tips, and it is characterized by the presence of large styles (370–1000/5.0–32.5 µm) in combination with oxeas of intermediate size (160–500/5.0–12.5 µm). This new species constitutes the first record of the genus for the Peruvian coast as well as for the entire Eastern Pacific.